2019
DOI: 10.1038/s41598-019-41462-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin native prefibrillar oligomers but not monomers induce membrane damage that triggers NMDA-mediated Ca2+-influx, LTP impairment and neurotoxicity

Abstract: Amyloid protein misfolding results in a self-assembling aggregation process, characterized by the formation of typical aggregates. The attention is focused on pre-fibrillar oligomers (PFOs), formed in the early stages and supposed to be neurotoxic. PFOs structure may change due to their instability and different experimental protocols. Consequently, it is difficult to ascertain which aggregation species are actually neurotoxic. We used salmon Calcitonin (sCT) as an amyloid model whose slow aggregation rate all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 71 publications
4
22
0
Order By: Relevance
“…In particular, partially structured and mainly disordered PFOs resulted to be able to damage the lipid bilayer by the formation of "amyloid-pores" and this was made possible by Chol that rendered fluid membranes. This is in good agreement with the biological results we recently published about Ca 2+ -influx induced damage in hippocampal primary neurons [20] and allows us to speculate about the molecular mechanisms at the basis of neurotoxicity. Structural results gave interesting information about the molecular mechanisms.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In particular, partially structured and mainly disordered PFOs resulted to be able to damage the lipid bilayer by the formation of "amyloid-pores" and this was made possible by Chol that rendered fluid membranes. This is in good agreement with the biological results we recently published about Ca 2+ -influx induced damage in hippocampal primary neurons [20] and allows us to speculate about the molecular mechanisms at the basis of neurotoxicity. Structural results gave interesting information about the molecular mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, in our previous paper concerning neurotoxicity in hippocampal neurons treated by sCT-PFOs we showed that, under physiological conditions, other cellular mechanisms were involved [20]. Nevertheless, in the same study we showed that the Ca 2+ -influx due to membrane permeabilization was the triggering factor that induced NMDA-mediated neurotoxicity and this is in good agreement with the results obtained now with both HT22-DIFF cells and liposomes.…”
Section: Neurotoxicitysupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, it has been reported that electrostatic interactions between sCT and GM1 (a ganglioside component of cellular membranes) which are stabilized by cholesterol cause spherical amyloid aggregation to occur on the surface of liposomes . In addition, hCT is capable to form channels within the membrane and cause ion leakage, and this hCT‐induced membrane pore formation is enhanced by the presence of cholesterol . Therefore, cholesterol may play a crucial role in modulating calcitonin amyloid formation and cellular toxicity in vivo .…”
Section: Introductionmentioning
confidence: 99%